"Everything Being Tangled Up in Every Other Thing": Class, Desire, and Shame in Michelle Tea's The Passionate Mistakes and Intricate Corruption of One Girl in America. (27th May 2018) - McKenna, Emma
Abstract : This article explores the relationship of shame to class and to desire in Michelle Tea's memoir The Passionate Mistakes and Intricate Corruption of One Girl in America . Through applying a class analytic to the framework of shame recently advanced by feminist, queer, postcolonial, and affect theorists, I foreground shame as central to the experience of being poor and queer, and examine shame as not only negative and positive, but as productive. I operationalize an "oppositional reading strategy" to insist on attention to the materiality of embodied desire and labor, in particular queer desire and sex work, that is made available in poor and working‐class women's life‐writing. Tea's memoir demonstrates how writing about an ambivalent relation to shame is an act of resistance, an opportunity to transform private, individual experiences into public, and therefore collective, articulations.